Trophic transfer of polybrominated diphenyl ethers in a recently modified freshwater food web from the St. Lawrence River, Canada. (September 2020) - Lapointe, Dominique; Pelletier, Magella; Paradis, Yves; Armellin, Alain; Verreault, Jonathan; Champoux, Louise; Desrosiers, Mélanie
Abstract: Introduction of invasive species can have a profound impact on food web structure and therefore on trophic transfer of contaminants. In the St. Lawrence River (Canada), 20 years after its first detection in the system, invasive round goby ( Neogobius melanostomus ) has become the main prey for several piscivorous species. To evaluate the accumulation, trophic transfer, and the ecological risk of polybrominated diphenyl ethers (PBDEs) in this recently modified freshwater food web, samples of sediment, invertebrates, fish and aquatic bird eggs and plasma were collected. Sampling sites were located upstream and at two locations downstream of the Montreal wastewater treatment plant outfall. The results suggest that the influence of the WWTP effluent on PBDEs concentrations varied among the various compartments of this recently modified freshwater food web. The results also suggest that although predatory fish have switched to consuming round goby as a prey item instead of native yellow perch, this new feeding behaviour is not expected to have important impacts on the level of transfer of PBDE within this food web. The biota-sediment accumulation factors (BSAFs) ranged from 0.6 to 436, whereas biomagnification factors (BMFs) varied between 0.2 and 475. Despite our conservative method of risk assessment, we calculated an important risk for piscivorous fish and gull eggs within this study area. Graphical abstract: Image 1 Highlights: PBDEs were detected at all levels of the St. Lawrence River food web. Switch from native prey to invasive round goby had little impact on PBDEs trophic transfer. Important risk for piscivorous fish and herring gulls near Montreal's effluent.